Schiff bases and their possible therapeutic applications: A review - Nidhi; Siddharam; Devendra Pratap Rao; Amit Kumar Gautam; Ashish Verma; Yashveer Gautam (Results in Chemistry)
Schiff base (SB) represents a category of organic compounds in which a nitrogen atom with a double bond maintains its stereochemistry. The long history of Schiff base has been fascinating chemists to explore its new dimension by generating optimal analogs with their therapeutic effects to serve the humankind. Schiff base coupled with metals evolves as a new stable molecule with their therapeutic indication either as antifungal, antibacterial, anticancer or antiproliferative agents. Fusion of Schiff base with heterocyclic compounds like pyrazole or imidazole moieties conjointly crop different molecular entities with antifungal properties. Similarly, the amalgamation of Schiff base with benzene derivatives yields a new molecule with high antibacterial properties. However, further structural optimization may showcase other antimicrobial activities to prove this molecular entity as a potential druggable candidate. Apart from these, the well-known Schiff base anticancer and antiproliferative properties of this molecular entity are being explored. Schiff base, however, is suspected of causing cancer and can cause severe eye discomfort.